Local Politics and a Self-assessment of Political Practice. Perspective of a Neighbourhood Leader in Mexico City on their Political Trajectory - Hélène Combes (Íconos)
This article analyses politics at the local level through the perspective of a neighbourhood leader in Mexico City. Drawing on the comprehensive sociology approach and the study of a specific career trajectory, it analyses how a neighbourhood leader works to construct beneficiaries for neighbourhood level social programs and broker resources that would not be leveraged without their work. The analysis presents an alternative vision to other analysts who have emphasized the capture of public funds for electoral purposes by neighbourhood leaders. The objective is to invite researchers to rethink the role of the local political ‘broker’ or intermediary and to consider the complexity of this role. The moral and political dilemmas that condition the behaviour of such leaders are also considered. From here, without making a moral judgement, we consider how political brokerage and the activities that it involves combine instrumental considerations with moral and ideological dimensions.